Prose of V.F. Mikhailov (Eurasian Journal of Philology Science and Education, 2018)
The article refers to the literary process of Kazakhstan of XXI centuryof modern Russian literature of Kazakhstan. About the founders of Russianliterature of Kazakhstan. On the change of genres, motifs in contemporaryRussian literature of Kazakhstan. The analysis on the documentary story VFMikhailov «Great jute». The fact that this book is the first, which was written in Russian about the terrible tragedy of Kazakhstan. The fact that thistragedy has affected not only the Kazakh people, but also many «specialsettlers», referring to the Kazakh land – Russian, Ukrainians and other nationalities. Also, the book reveals the fact that hunger was made by hand,that is to say, it was the result of violence.